THE CONTRIBUTION OF THE LAMPULO FISHING PORT, FOR FISHERY SECTOR IN BANDA ACEH CITY, NANGGROE ACEH DARUSSALAM PROVINCE - Lubis, Abdillah Muhammad; ', Syaifuddin; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in January precisely on 21 January until 10 February 2015 atLampulo fishing port, Banda Aceh. the purpose of this study is to obtain data and informationabout contribution of the Lampulo fishing Port for fishing catch in Banda Aceh. Variousinformation is needed namely, the number of fishermen, the number of fishing gear and boats,total production of fishery products and the Port Lampulo income which is then compared withthe fisheries sector Banda Aceh, Lampulo fishing port contribution to the fisheries sector is 72-78% the number of fishermen, number of fleets 56-76%, 56-75% the amount of fishing gear, fishproduction contributes 74-99% and contributions PP Lampulo for 42-53% of regional revenue, ifthe contribution of the port of> 5%, then there is an opportunity to continue to develop in apositive direction if <5%, it is unlikely the port will increase its revenue in the future.Keyword: PP Lampulo, Contribution, Banda Aceh, Fishery Sector